2018
DOI: 10.1371/journal.pone.0193523
|View full text |Cite
|
Sign up to set email alerts
|

A novel learning algorithm to predict individual survival after liver transplantation for primary sclerosing cholangitis

Abstract: Deciding who should receive a liver transplant (LT) depends on both urgency and utility. Most survival scores are validated through discriminative tests, which compare predicted outcomes between patients. Assessing post-transplant survival utility is not discriminate, but should be “calibrated” to be effective. There are currently no such calibrated models. We developed and validated a novel calibrated model to predict individual survival after LT for Primary Sclerosing Cholangitis (PSC). We applied a software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 28 publications
(26 reference statements)
0
23
0
Order By: Relevance
“…In addition to these evaluations using the discriminative concordance measure, we also applied a calibration measure: “D-Calibration” (“D” for “Distribution”) [15, 16], which measures how well a individual survival distribution model is calibrated, using the Hosmer-Lemeshow (HL) [30] goodness-of-fit test; see Appendix B.2. We found that all of our models, for both datasets (METABRIC and KIPAN), passed this calibration test; see Appendix C.2, especially Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these evaluations using the discriminative concordance measure, we also applied a calibration measure: “D-Calibration” (“D” for “Distribution”) [15, 16], which measures how well a individual survival distribution model is calibrated, using the Hosmer-Lemeshow (HL) [30] goodness-of-fit test; see Appendix B.2. We found that all of our models, for both datasets (METABRIC and KIPAN), passed this calibration test; see Appendix C.2, especially Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…We show that this predictor performs better than other standard survival analysis tools in terms of concordance. We also found that it was “D-calibrated” [15, 16]; see Appendix B.2.…”
Section: Introductionmentioning
confidence: 95%
“…In sensitivity analyses, the algorithm remained accurate regardless of baseline phenotype of PSC, degree of bilirubin elevation, or hepatic involvement. In an attempt to identify those patients with PSC most likely to survive post‐LT, Andres et al produced a novel multitime point calibrated model for the prediction of individual survival after LT derived from Scientific Registry of Transplant Recipients (SRTR) database information for 2,769 PSC LT recipients . This model was able to outperform traditional Cox regression analysis in evaluation of long‐term survival for PSC LT recipients.…”
Section: Pscmentioning
confidence: 99%
“…Regarding primary sclerosing cholangitis, a team of researchers derived and validated a risk estimate tool based on GB algorithms to predict the outcomes of the disease[ 155 ]. In a different study, an ML model was developed to predict survival curves for patients with primary sclerosing cholangitis following liver transplantation[ 156 ]. The P value of the χ 2 test of the distributional calibration was 1, indicating excellent calibration of the model[ 156 ].…”
Section: Applications Of Ai In Hepatologymentioning
confidence: 99%